Pengaruh Situasi Kompetisi Kerja dan Dukungan Sosial Keluarga Terhadap Fear Of Success Pada Wanita Bekerja - Sitepu, Linda; Zulkarnain, Zulkarnain; Zahreni, Siti (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2017)
The change of culture from traditional to modern society has impacted to women ingetting their career.The other hand, some people views working women as against her nature and obligation as a woman. The difference in this paradigm forces women in to fear of success. The purpose of this study was to determine the influence of competitive work situation and family social support toward fear of success among female employees. The study involved 106 marketing staffs at Finance company and data was collected through scales of competitive work situation, family social support and fear of success. The results of multiple regression analysis showed that competitive work situation and family social support influenced significantly toward fear of success among female employees. The competitive work situation and the family social support contributed in decreasing fear of success. The implication of this research is expected that organizations to create an organizational environment that triggers workers to achieve more by providing feedback, couching and counseling to decrease fear of success among female employees.